Nasi Lemak International / Mohamad Hafeez Abdul Halim... [et al.] - Abdul Halim, Mohamad Hafeez; Jusuh, Ahmad Nuzul Anwar; Hussin, Amirul Azam; Shamsul Bahari, Ammar Shafidz; Mohd Hanafiah, Ellyas (2006)
Nasi Lemak International is a bumiputra company which is provide local food “Nasi Lemak” in a new way. In ensuring that the restaurant runs smoothly, the operating plan needs to be planned as best as possible. Due to the busy current trend of society, the way Nasi lemak is prepared needs to be like a fast food. This restaurant situated at Kulim, Kedah.